The composition of aid and the fiscal sector in aid-recipient economy: A model - George Mavrotas; Banzoumana Ouattara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Building on recent work in the fiscal response literature, the present paper develops a new fiscal response model, which, for the first time in the relevant literature, combines the ideas of both endogenous and disaggregated aid. We endogenized aid on the grounds that the recipient government has some influence over aid disbursements. Regarding aid disaggregation, it is argued that each of the main four categories of aid, namely project aid, programme aid, technical assistance and food aid may exert different effects on the recipient economy. Furthermore, in case the preferences of the aid-recipient government are higher for some of these types of aid, neglecting aid disaggregation would lead to aggregation bias in the results and conclusions. The model adds an important new dimension to the vast aid effectiveness literature and calls for further modelling as well as empirical work in this promising research area so that significant policy implications can be derived.
Keywords: F35; 330; foreign aid; fiscal sector; fiscal response literature; aid effectiveness; Entwicklungshilfe; Theorie